Pluralité des cultures dans l’oeuvre de Michel Houellebecq et de Jerzy Pilch - Hładki, Paweł (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
This article discusses the representation of cultural plurality in the novels of two major French and Polish contemporary fiction writers: Michel Houellebecq and Jerzy Pilch. The aim of this essay it to present a comparative analysis of the different conceptions represented by these two writers. The influence of historical, cultural and religious particularities on Pilch's and Houellebecq's views on multiculturalism is also considered. Furthermore, by comparing Jerzy Pilch’s and Michel Houellebecq’s work, we examine two different perspectives: the first one, that of a member of a Polish religious minority, i.e. a Protestant and the second one, that of a notorious racist and Islamophobe.